Studying the Parameters and Reliability of the System of Small Intensity Irrigation for Work in the Conditions of Mining Agriculture in Azerbaijan. - Aliyev, Prof.RAE. Z.H. (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2019)
The article discusses the issues of scientific and theoretical justification for the use of automated irrigation in agriculture, that these systems can reduce the capital costs of their construction, as well as ensure the principle of "rain" and "drip irrigation" with daily water consumption of plants. There are optimal conditions for the growth and development of plants during their growing season. It is proved that the automated irrigation of agricultural crops establishes high yields and increased labor productivity. Therefore, the elements and devices of the used automatic machine require a reliable and uninterrupted operation. This is due to the fact that the problem is that the problem lies not only in technical reliability but also in economic efficiency. , including micro-irrigation systems. Reliability, performance, and performance. Initially, the existing irrigation technique, stationary irrigation system consisted of a large number of elements of the same type, necessary for conducting field cultural events.